A comparison between effects of linear and non-linear mechanistic behaviour of materials on the layered flexible pavement response - Ghadimi, Behzad; Nikraz, Hamid; Leek, Colin; Nega, Ainalem (Trans Tech Publications Inc, 2013)
Modelling granular pavement materials has a significant role in the pavement design procedure. Modelling can be through an experimental or numerical approach to predict the granular behaviour during cyclic loading. The current design process in Australia is based on linear elastic analysis of layers. The analysis is performed through a well-known program CIRCLY which is applied to model bound pavement material behaviour. The KENLAYER is one of the common pavement software models used for pavement design in the United States which performs non-linear analysis for granular materials. Alternatively, a general Finite Element program such as ABAQUS can be used to model the complicated behaviour of multilayer granular materials. This study is to compare results of numerical modelling with these three programs on two sample pavement models.